2011
DOI: 10.1002/jsfa.4435
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of marine collagen peptides from Chum Salmon skin enhances cutaneous wound healing and angiogenesis in rats

Abstract: The results show the efficacy of oral MCP treatment on wound healing in animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 31 publications
6
53
0
1
Order By: Relevance
“…Our current findings confirm previous reports from experimental and animal trials demonstrating the stimulatory effects of collagen peptides on anabolic processes supporting the maintenance of the dermis extracellular matrix [6,7,8,9,20]. Our in vitro studies on primary human dermal fibroblasts demonstrated a stimulatory effect of Verisol® on the expression of skin extracellular matrix macromolecules.…”
Section: Discussionsupporting
confidence: 91%
“…Our current findings confirm previous reports from experimental and animal trials demonstrating the stimulatory effects of collagen peptides on anabolic processes supporting the maintenance of the dermis extracellular matrix [6,7,8,9,20]. Our in vitro studies on primary human dermal fibroblasts demonstrated a stimulatory effect of Verisol® on the expression of skin extracellular matrix macromolecules.…”
Section: Discussionsupporting
confidence: 91%
“…This is a special staining for collagen fibers that makes their color blue. Then, based on the intensity of blue color (Zhang et al, 2011), scaling was numbered as follows; 1: rare, 2: minimal, 3: moderate, 4: marked, 5: high marked.…”
Section: Histological Evaluationmentioning
confidence: 99%
“…Due to the special marine ecological environment, such as high pressure, low temperature and high salinity, MCPs from marine fishes differ greatly from those from terrestrial livestock in both physicochemical properties and amino acid compositions, and have unique physiological functions including antibacterial [19], antioxidant [16,20], antihypertensive [21,22,23], neuroprotective [24] and anti-skin-aging activities [25]. It was reported that oral administration of marine collagen peptides from Chum Salmon ( Oncorhynchus keta ) skin enhanced cutaneous wound healing and angiogenesis in rats [26]. Most recently, the electrospun tilapia collagen nanofibers which could accelerate skin wound healing rapidly and effectively in the rat model were developed [27].…”
Section: Introductionmentioning
confidence: 99%